Canine Width as a Means for Stature & Sex Prediction (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Estimation of stature, along with sex, age and race, is one of the four pillars of forensic anthropology and is considered a preliminary screening in identification of skeletal remains. Teeth, particularly the canines form an excellent material for such forensic investigations as they resist decay due to caries or other diseases of tooth as well as remain highly stable during natural calamities. Materials & Method: Study was conducted in SSSMC, Dehradun among 100 healthy subjects (>17 years), comprising 66 males and 34 females. Mean mesio-distal width of mandibular canine tooth was measured on both side on dental casts and mean stature measured by anthropometer. The collected data was subjected to statistical analysis; correlation and sexual dimorphism was calculated for both sexes and a linear regression formula obtained for estimating stature. Observations & Result: Mean canine width on both right and left side as well as height was more in males as compared to females. Sexual dimorphism was more involving right canine width. The findings were found to be statistically significant for right canine width (RCW) and for height, between male and females. Accuracy for sex prediction was high in females (F= 64.7%, M=59.1%). Using the values of RCW and LCW, regression equations were obtained for estimating height. Conclusion: Width of mandibular canine is reliable for stature estimation but for sex prediction it is not much reliable on the left side. However these parameters can be used as an adjuvant in situations when only single tooth is available for identification.